A prospective study of the incidence of drug‐induced liver injury by the modern volatile anaesthetics sevoflurane and desflurane. Issue 7 (13th February 2019) - Bishop, Bridget; Hannah, Nicholas; Doyle, Adam; Amico, Francesco; Hockey, Brad; Moore, David; Sood, Siddharth; Gorelik, Alexandra; Liew, Danny; Njoku, Dolores; Nicoll, Amanda
Summary: Background: Volatile anaesthetics are known to cause drug‐induced liver injury, a hepatotoxic reaction characterised by antibodies to trifluoroacetylated lipid and protein adducts and cytochrome p450 2E1. The incidence of volatile anaesthetic drug‐induced liver injury from older agents has been described, but modern agents have not been prospectively studied. Aim: To determine prospectively the incidence of volatile anaesthetic drug‐induced liver injury from sevoflurane and desflurane. Methods: Adult surgical patients with a predicted post‐operative stay of at least 4 days were recruited. If volatile anaesthetic was administered, liver biochemistry was performed regularly. Medications, observations and other investigations were documented. Patients with abnormal liver biochemistry were classified as likely volatile anaesthetic drug‐induced liver injury or not based on clinical assessment, Roussel Uclaf Causality Assessment Method score, and the absence of other likely pathology. Some patients were also tested for antibodies to both trifluoroacetylated lipid and protein adducts, and cytochrome p450 2E1. Results: A total of 209 patients were recruited, of which 121 were included for analysis. Post‐operative liver biochemistry was abnormal in 62 patients (51.2%); further classified as not volatile anaesthetic drug‐induced liver injury in 47 cases (38.8%), and likely volatile anaesthetic‐drug induced liver injury in 15 cases (12.4%). Of the likely volatile anaesthetic drug‐induced liver injury patients, only one had severe disease with alanine transaminase greater than five times the upper limit of normal, while four cases had moderate disease with alanine transaminase greater than three times the upper limit of normal. Thus, the incidence of clinically significant volatile anaesthetic drug‐induced liver injury was 4.1%. No risk factors were identified. Conclusions: Volatile anaesthetic drug‐induced liver injury from modern agents seems to be as common (4.1%) as previously reported with older agents (3%), and may identify patients at risk of severe acute liver injury with subsequent re‐exposure.